Nano-phononic metamaterials enable an anomalous enhancement in the interfacial thermal conductance of the GaN/AlN heterojunction - Wu, Cheng-Wei; Pan, Hui; Zeng, Yu-Jia; Zhou, Wu-Xing; Chen, Ke-Qiu; Zhang, Gang (Nanoscale, 2023)
Improving the interfacial thermal conductance (ITC) is very important for heat dissipation in microelectronic and optoelectronic devices. In this work, taking GaN-AlN contact as an example, we demonstrated a new mechanism to enhance the interfacial thermal conductance using nano-phononic metamaterials. First, how a superlattice affects the ITC is investigated, and it is found that with decreasing superlattice periodic length, the ITC first decreases and then increases, because of the coherent phonon interference effect. However, although constructing a superlattice is effective for tuning the ITC, it cannot enhance the ITC. We suggest that the ITC can be enhanced by 9% through constructing an interfacial nano phononic metamaterial, which is contributed by the additional phonon transport channels for high-frequency phonons with a wide incidence-angle range. These results not only establish a deep understanding of the fundamental physics of the interfacial thermal conductance, but also provide a robust and scalable mechanism, which provides a degree of freedom for efficient thermal management. Improving the interfacial thermal conductance (ITC) is very important for heat dissipation in microelectronic and optoelectronic devices.